Hubungan Antara Bimbingan Belajar dan Motivasi Belajar dengan Prestasi Belajar Siswa di MI Nidhomiyah Jombang - Miftahillah Miftahillah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2014)
With many appearing tutoring then expected to increase learning achievement student. Achievement of learning achieved by student is influenced by several factors, among them tutoring and motivation learning. The problem in this research is the relationship between tutoring and motivation learning to learning achievement student MI Nidhomiyah Jombang. The purpose of this study was to determine the relationship between tutoring and motivation learning to learning achievement student MI Nidhomiyah Jombang. This research is taking the entire population of the sixth grade students at MI Nidhomiyah Jombang academic years 2011/2012, amounting to 30 students, the data sampling technique used in this study is a questionnaire technique and documentation, with using SPS Sutrisno Hadi and Yuni Pamardiningsih, Psychology UGM Yogyakarta. Conclusion simultaneously with R2 = 0.312 F = 6.131 with p=0.007 (p 0.05, and X2Y there is correlation very significant r = 0.556 with p = 0,002 where p<0.01.